2002
DOI: 10.1007/s11661-002-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of elastic and plastic anisotropy on the flow behavior in a duplex stainless steel

Abstract: The load partitioning between two phases in a cold-rolled duplex stainless steel has been experimentally studied in situ by X-ray diffraction, for different loading directions. It was found that the load partitioning between the two phases is dependent on the loading direction. For loading in the rolling direction, both phases deform plastically to the same degree, while more plastic deformation occurs in the austenitic phase during loading in the transverse direction. For loading in the 45-deg direction, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…The features of a strong bcc -fiber (f100gh011i-f211gh011i-f111gh011i) and an undevelopedfiber (f111gh011i-f111gh112i) in the final annealed sheets are similar to the previous studies. [4][5][6][7][8][9][10] The orientation density increased with increasing cold-rolling reduction. The main orientation is f100gh011i at a 67% cold-rolling reduction, while it is f211gh011i at 78% and 89% cold-rolling reductions.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The features of a strong bcc -fiber (f100gh011i-f211gh011i-f111gh011i) and an undevelopedfiber (f111gh011i-f111gh112i) in the final annealed sheets are similar to the previous studies. [4][5][6][7][8][9][10] The orientation density increased with increasing cold-rolling reduction. The main orientation is f100gh011i at a 67% cold-rolling reduction, while it is f211gh011i at 78% and 89% cold-rolling reductions.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…As both the and phases are elongated along the longitudinal direction unlike single-phase materials, a shape factor of the phase or grain boundaries should be considered for DSS sheets. From the viewpoint of the morphological contribution, Moverare et al 8) presented that for loading at the 45 direction, the Texture and Planar Anisotropy of r-Value in Duplex Stainless Steel Sheetdirection of maximum shear stress was oriented to the same direction as the elongated microstructure and the slip lines extended over a greater distance compared with loading at the rolling and transverse directions. Further investigations in consideration of the morphology and observations of the deformation structure are required in future to realize the precise prediction of plastic anisotropy in DSS sheets.…”
Section: Predictions Of R-valuementioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] When materials are applied to sheet products, sheet formability and anisotropy in addition to strength and elongation are important, and there are few reports about the formability of standard DSS sheets. [11][12][13][14][15][16] According to these findings, it has been reported that high-alloy DSS sheets have a large planar anisotropy and their texture is different from that of single-phase materials, [11][12][13][14][15][16] but studies on the texture and planar anisotropy of the lean DSS sheets are not found.…”
Section: Introductionmentioning
confidence: 99%